Profit Optimization of Sambal SohibKoe Using Linear Programming Simplex Method - Charles Nicole; Christopher Vergara Lidaya; Dudy Effendy; Feby Lia; Felix Kharisma; Khefen; Meilisa Permata Wonowijaya (MultiTech Publisher, 2023)
Mrs. Devi's Sambal business named